1989
DOI: 10.1073/pnas.86.23.9524
|View full text |Cite
|
Sign up to set email alerts
|

Two epithelial tumor cell lines (HNE-1 and HONE-1) latently infected with Epstein-Barr virus that were derived from nasopharyngeal carcinomas.

Abstract: Two epithelial tumor cell lines were established from biopsy specimens of nasopharyngeal carcinomas (NPC). The specimens were taken from poorly differentiated squamous cell carcinomas ofthe nasopharynx. The tissues were prepared for cell culture and eventually two continuous epithelial cell lines were obtained and designated HONE-1 and HNE-1. Light and electron microscopic examination of these two cell lines demonstrated cells with an epithelial morphology including the presence of desmosomes. The HNE-1 cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(163 citation statements)
references
References 20 publications
2
161
0
Order By: Relevance
“…Cell lines, tumor and normal tissue samples Cell lines used were: 12 NPC (C666-1, CNE-1, CNE-2, HK1, HNE1, HNE2, HNE3, HONE1, TW-01, BM1, 5-8F and 6-10B) (Glaser et al, 1989;Qiu et al, 2004;Ying et al, 2005), 15 esophageal (EC1, EC18, EC109, HKESC1, HKESC2, SLMT-1, KYSE30, KYSE70, KYSE140, KYSE150, KYSE180, KYSE270, KYSE410, KYSE510 and KYSE520) (Tang et al, 2001;Ying et al, 2006), nine breast (MCF7, ZR-75-1, MB-231; T47D, MB-468, MB-435, SKBR3, BT549, and YCC-B2) (Kim et al, 2005;Ying et al, 2005) and eight cervical carcinoma (HeLa,Caski,C33A,SiHa,808,866,879 and 915) (Steenbergen et al, 2004;Ying et al, 2006). NP69, an SV40 Tantigen-immortalized nasopharyngeal epithelial cell line with many features of normal nasopharyngeal epithelial cells was used as a 'normal' control for NPC (Tsao et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Cell lines, tumor and normal tissue samples Cell lines used were: 12 NPC (C666-1, CNE-1, CNE-2, HK1, HNE1, HNE2, HNE3, HONE1, TW-01, BM1, 5-8F and 6-10B) (Glaser et al, 1989;Qiu et al, 2004;Ying et al, 2005), 15 esophageal (EC1, EC18, EC109, HKESC1, HKESC2, SLMT-1, KYSE30, KYSE70, KYSE140, KYSE150, KYSE180, KYSE270, KYSE410, KYSE510 and KYSE520) (Tang et al, 2001;Ying et al, 2006), nine breast (MCF7, ZR-75-1, MB-231; T47D, MB-468, MB-435, SKBR3, BT549, and YCC-B2) (Kim et al, 2005;Ying et al, 2005) and eight cervical carcinoma (HeLa,Caski,C33A,SiHa,808,866,879 and 915) (Steenbergen et al, 2004;Ying et al, 2006). NP69, an SV40 Tantigen-immortalized nasopharyngeal epithelial cell line with many features of normal nasopharyngeal epithelial cells was used as a 'normal' control for NPC (Tsao et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Among the cell lines that were employed in this study, HONE1 and C666 cells are poorly differentiated and are EBV positive. 33,34 HK1 is well differentiated and EBV negative. 35 Our results showed that anti-miR-200c transfection decreased cell growth, invasion, and migration, while miR-200c overexpression accelerates these processes.…”
Section: Discussionmentioning
confidence: 99%
“…The new aberrations (Supplementary Table S2 Cyclin B1 knockdown reinforces G 2 checkpoint function and reduces centromeric instability in cancer cells We next tested the impact of G 2 checkpoint defect on centromeric instability in cancer cells. Three cancer cell lines of different cell types: HeLa (cervical cancer), SLMT-1 (esophageal cancer) (Tang et al, 2001) and HNE-1 (nasopharyngeal cancer) (Glaser et al, 1989) were examined. Although cancer cells are known to retain some degree of G 2 checkpoint function, we anticipated that the G 2 checkpoint in cancer cells may not be as stringent as in normal cells.…”
Section: Resultsmentioning
confidence: 99%